An Efficient Conjugation Approach for Coupling Drugs to Native Antibodies via the PtII Linker Lx for Improved Manufacturability of Antibody–Drug Conjugates. (20th January 2021) - Merkul, Eugen; Muns, Joey A.; Sijbrandi, Niels J.; Houthoff, Hendrik‐Jan; Nijmeijer, Bart; van Rheenen, Gerro; Reedijk, Jan; van Dongen, Guus A. M. S.
Abstract: The Pt II linker [ethylenediamineplatinum(II)] 2+, coined Lx, has emerged as a novel non‐conventional approach to antibody–drug conjugates (ADCs) and has shown its potential in preclinical in vitro and in vivo benchmark studies. A crucial improvement of the Lx conjugation reaction from initially <15 % to ca. 75–90 % conjugation efficiency is described, resulting from a systematic screening of all relevant reaction parameters. NaI, a strikingly simple inorganic salt additive, greatly improves the conjugation efficiency as well as the conjugation selectivity simply by exchanging the leaving chloride ligand on Cl‐Lx‐drug complexes (which are direct precursors for Lx‐ADCs) for iodide, thus generating I‐Lx‐drug complexes as more reactive species. Using this iodide effect, we developed a general and highly practical conjugation procedure that is scalable: our lead Lx‐ADC was produced on a 5 g scale with an outstanding conjugation efficiency of 89 %. Abstract : Pt II complexes containing a payload, a bidentate ligand, and a halido leaving ligand (Cl −, Br − or I − ) can be conjugated to native monoclonal antibodies in a very efficient way by using iodide salts, such as NaI, as simple inorganic additives to the aqueous conjugation mixtures. This method works reliably for various mAbs, consistently giving conjugation efficiencies in the range of 75–90 %.